A retrospective study of pelvic limbs fracture management in avian species presented to University Veterinary Hospital (UVH) Universiti Putra Malaysia - Ismail, Siti Sarismahanim (2014)
In Malaysia. Avian Orthopedic is a remote field in Veterinary Medicine therefore most of the cases will be referred to University Veterinary Hospital (UVH). Universiti Putra Malaysia for further diagnostic work out and treatment. This is a retrospective study to determine the common pelvic limbs fracture cases in avian species presented to UVH form year 2009 to 2013 and to study the clinical pattern of each management of pelvic limbs fracture and the outcome of each management and factor influencing the outcome. For this study. the data was chosen from the birds (pets or wild birds) that presented with pelvic limbs fracture from year 2009 to 2013 (5 years).Patient Medical Record (PMR) for each case was carefully assessed retrospectively. Radiograph was not available for all cases; therefore PMR was used as the main information data. The main data collections for this study were subdivided into four categories; patient data, fractured bone data, clinical management data, healing progress and outcome data. Results were analyzed using software IBM®SPSS® Statistics 20 System © Copyright IBM Corporation 1989, 2011. There were 36 birds (pet and wild birds) with 47 fractured limbs with complete inclusion criteria being evaluated in this study. The findings showed that the most common fractured bone was tibiotarsal (n=36/47 [78.72%]). The stabilization fractures method chosen, were highly significant with the body weight of the birds (P= 0.002) and the duration of fracture (fracture's age) P Value was below 0.001. There are no significant differences of fracture stabilization method between pet birds and wild birds, between type of fracture or bone involved. 98% (n=46/47) of birds healed, from that 98%,49% (n=23/47) healed within 3 to 6 weeks post stabilization. Healing period and target of healing (3 to 6 weeks) was significantly correlated with the duration of fractured bone, total number of fracture sites per bird, fracture types (open or close fracture), clinical management inclusive of stabilization method, supportive medication; antibiotic, anti-inflammation and nerve supplement (P<0.050). Meanwhile 60% (n=28/47) had an excellent therapy outcome. In conclusion, a successful of clinical management of avian species fracture lies on various factors, the correct stabilization method with supportive treatment will increase the chances of a successful healing with excellent therapy outcome. Close fracture, short duration of fracture, and a single fracture site will increase the healing process.